Two-Year Visual Outcomes of Evolution Implantable Collamer Lens and Small Incision Lenticule Extraction for the Correction of Low Myopia - Fu, Mengjun; Li, Meiyan; Xian, Yiyong; Yu, Zhiqiang; Zhang, Haorun; Choi, Joanne; Niu, Lingling; Wang, Xiaoying; Zhou, Xingtao (Frontiers in Medicine, 2022)
Introduction: To investigate the 2-year visual quality of EVO-ICL and SMILE for the correction of low myopia. Methods: In this prospective study, we included 25 eyes of 25 patients (7 males) who underwent EVO-ICL and 36 eyes of 36 patients (16 males) who underwent SMILE between January 2018 and December 2018. Subjective and objective visual outcomes were compared between ICL and SMILE. All patients were followed for two years. Results: The percentage of patients with UDVA greater than or equal to preoperative CDVA was comparable in the ICL group 80% (20/25) and SMILE group 88.89% (32/36). SE was within ±0.50D in 96% (24/25) of the ICL group and 94.44% (34/36) of the SMILE group. No eye lost more than 2 lines of CDVA. Postoperative HOAs were significantly increased in the ICL group (P < 0.01) and in the SMILE group (particularly in vertical coma) (P < 0.01). The most common visual complaint was halo after ICL, and starburst after SMILE. There was no correlation between HOAs and visual complaints (P > 0.05). Conclusions: EVO-ICL provides comparable safety, efficacy, long-term visual stability and high patient satisfaction compared to SMILE in correcting low myopia. EVO-ICL could be a favorable alternative for low myopia.